ANALISIS PENGARUH KUALITAS LAYANAN, KEPUASAN DAN EXPERIENTIAL MARKETING TERHADAP ELECTRONIC WORD OF MOUTH LAZADA ONLINE SHOP - Lufiana Ikasanti; N Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This research aims to test and analyze the influence of quality of service, satisfaction, and experiential marketing against electronic word of mouth Lazada online shop. Population and samples are 80 online user shop Lazada. Collection of data through the questionnaire. The data analysis in this study is SPSS help version 14. Testing practical use of the data study used is includes validity test, reliability test, normality test, path test, T-Test, and Sobel test. The results of analysis (path analysis) that the quality of service and Experiential Marketing affect the satisfaction , Quality of service and Experiential Marketing affect the Electronic Word Of Mouth , Satisfaction) Affect the Electronic Word Of Mouth , and the quality of Service and Experiential Marketing affect the Electronic Word Of Mouth through Satisfaction.Keywords:Quality of service, Experiential Marketing, Electronic Word Of Mouth, Satisfaction.